2020
DOI: 10.34297/ajbsr.2020.11.001617
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Metastasis of Breast Cancer: A Case Report and Literature Review

Abstract: Choroid is a very rare site of metastases but the most primary cancers leading to choroidal metastases are breast cancer then lung cancer. Generally, choroidal metastases occur late the course of cancer in the presence previously of other metastatic sites, and they were associated with poor prognosis. We report the case of a patient followed in Medical Oncology Department of Fes, for breast cancer who presented visual disorders leading to the diagnosis of choroidal metastasis. The aim of this work is to report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, recent developments in the therapy of BC and management of metastatic diseases, led to an increase in the 5year breast-cancer-specific survival from 74.0% during 1975 to 1979 [19] to 90% in 2016, according to Surveillance, Epidemiology and End Results (SEER) data [9,19,20]. The estimated incidence of choroidal metastases in patients with disseminated BC varies from 2 to 13% in different studies [8,52]. In a study by Wiegel et al [52], asymptomatic BC choroidal metastasis (CM) was observed in 11% of patients with more than one affected organ and the risk factors associated with choroidal metastases were pulmonary and cerebral dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent developments in the therapy of BC and management of metastatic diseases, led to an increase in the 5year breast-cancer-specific survival from 74.0% during 1975 to 1979 [19] to 90% in 2016, according to Surveillance, Epidemiology and End Results (SEER) data [9,19,20]. The estimated incidence of choroidal metastases in patients with disseminated BC varies from 2 to 13% in different studies [8,52]. In a study by Wiegel et al [52], asymptomatic BC choroidal metastasis (CM) was observed in 11% of patients with more than one affected organ and the risk factors associated with choroidal metastases were pulmonary and cerebral dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that patients with breast cancer are exposed to a lot of stress that can cause psychological and social disorders in their lives.The most important risk factors for breast cancer are age, sex, family history of cancer, and hormonal factors. Fortunately, cancer treatment has progressed amazingly, surgery, chemotherapy, and radiotherapy can destroy tumors and arrest cancer progression [28,29]. In recent years, the use of nanotechnology to diagnose and treat cancer has made significant progress [30][31][32].…”
mentioning
confidence: 99%